THE CONCEPTS OF «LONELINESS» AND “PARTING” IN THE UZBEK AND ENGLISH LANGUAGES (TAMADDUN NURI JURNALI, 2024)
Scientists are interested in both the social conditions that cause loneliness and people’s assessment of their social reality. Today, there is a need for a complete, systematic definition of loneliness and its unified conceptual application. This approach required a new methodological approach to studying the phenomenon of loneliness. This is one of the aspects of the scientific novelty of the study. The fact is that existing approaches to the study of loneliness do not fully reflect the complexity of the structure of the phenomenon of loneliness. Psychodynamic model. In this model, loneliness is considered as an emotional experience.